Pengujian Black Box pada Aplikasi Sistem Informasi Akademik Menggunakan Teknik Equivalence Partitioning - Dwi Bahar Muslimin; Dwi Kusmanto; Karina Femi Amilia; Muhammad Syamsul Ariffin; Siti Mardiana; Yulianti Yulianti (Teknik Informatika Universitas Pamulang, 2020)
The purpose of this study is to assist MTS Al-Hidayah in school academic management which is focused on school info, lesson schedules, school activities, facilitating data search, and producing accurate reports. In the academic information system at the school there are still many shortcomings when validating the data to be entered, so that it can cause the data stored in the database to be incompatible with the expected data. So it is proposed testing using the Black Box method based on Equivalence Partitioning as a whole regarding the use, benefits, and results obtained from the useof the software. Equivalence Partitioning Technique that discusses testing in the aspect of validation enter seen from a valid class. The results of this study can be concluded that the results of testing the accuracy of the school information system software at MTS Al-Hidayah will provide the best solution for the school for the future.The purpose of this study is to assist MTS Al-Hidayah in school academic management which is focused on school info, lesson schedules, school activities, facilitating data search, and producing accurate reports. In the academic information system at the school there are still many shortcomings when validating the data to be entered, so that it can cause the data stored in the database to be incompatible with the expected data. So it is proposed testing using the Black Box method based on Equivalence Partitioning as a whole regarding the use, benefits, and results obtained from the useof the software. Equivalence Partitioning Technique that discusses testing in the aspect of validation enter seen from a valid class. The results of this study can be concluded that the results of testing the accuracy of the school information system software at MTS Al-Hidayah will provide the best solution for the school for the future.